Gaya Kepemimpinan Influence Untuk Meningkatkan Kuantitas Peserta Didik Di Smks Sagaranten - Jalaludin Bulkini; Mulyawan Safwandy Nugraha (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Leadership is a complex and unique phenomenon of social interaction, anyone will show leadership behavior when interacting in a format that influences others. Even in personal capacity, in the human body there is capacity or potential as a controller, which essentially facilitates a person to be able to lead himself.This research journal was conducted at SMKS Sagaranten which is located on the cigadog highway km.2 sagaranten sukabumi and produces the influence of the principal's leadership to increase the quantity of students.Leadership is often given the meaning of degree of influence, while the leader is the person who has the most potential to influence. Leaders who cannot actualize their influence do not have the character of true leadership. Then we must know how educational leadership is so the purpose of this article is to dig deeper into leadership and complete the task. Articles are made with techniques for gathering resources such as reading material and books on leadership.So that we can draw the conclusion that educational leadership as "one ability and process of influencing, guiding, coordinating and mobilizing other people who are related to the development of the science of education and the implementation of education and teaching, so that the activities carried out can be more efficient and effective in achieving educational and teaching goals.